Formação continuada de professores da educação básica da rede municipal de ensino de Goiânia - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
This dissertation directed to the Interdisciplinary Postgraduate Program in Education, Language and Technology at State University of Goiás – PPG-IELT is linked to the Education, School and Technologies line and the thematic axis Educational Public Policies / Higher Education / Education and Work under the theme of Continuing Training and Educational Policies regarding the Continuing Training of Basic Education teachers. In this research, the main question is how the continued training of Basic Education teachers in the Goiânia Municipal Education Network takes place. This question results in the following investigation: how is the offering and evaluation of complementary continuing education courses for Basic Education teachers offered by the Training Management (GERFOR) in the Municipal Education Network of Goiânia? This study has the general objective of analyzing the continuing training of Basic Education teachers in the municipal network of Goiânia, offered by GERFOR in the period from 2018 to 2022. To achieve this objective, we sought to explore the continuing training of teachers in the light of public educational policies; analyze the continuing training of teachers in the federal and municipal spheres in Brazilian educational legislation and finally analyze the complementary courses offered by GERFOR for the continuing training of Education professionals at SME/Goiânia in the period from 2018 to 2022. The methodological approach is qualitative, in the bibliographic and documentary type, guided by Minayo (2002) and Marconi and Lakatos (2003) on the paths and processes of qualitative research. The initial theoretical support for the discussion about teacher training runs through Freire (1992-2018), Imbernón (2010), Gatti, Barreto and André (2009-2019), Nóvoa (2017), Tardif (2014), Shiroma (2002), Libâneo (2018), Laval (2019) among others. The initial choice of these authors is justified because they present reflections on the teaching work and continuing education from criticism to humanistic perspective, considering the personal and professional development of teachers in different contexts. In summary, the results showed that there are challenges in implementing educational policies in Goiânia, highlighting a limited vision of training, a predominantly technical perspective, and a lack of critical reflection towards a comprehensive approach, with effective monitoring of teachers who undertake training activities and who can participate in the development of new courses through systematic assessments of the coverage achieved by the courses. Furthermore, the economic justifications presented by the municipality, especially in the context of the pandemic, aiming to deny, restrict access to continuing education or monitor teachers' non-completion of their courses, reveal a disconnection between the intentions expressed in the Municipal Education plan PME-Goiânia and the reality faced by the educators.
Continuing training of basic education teachers in the municipal education network of Goiânia
Keywords: Formação Continuada de Professores - Políticas Públicas Educacionais; Formação Continuada de Professores - GERFOR - Goiânia(Goiás); Continuing Teacher Training - Educational Public Policies; Continuing Teacher Training - GERFOR - Goiânia(Goias); CIENCIAS HUMANAS::EDUCACAO